Monitoring cytochrome P450 activity in living hepatocytes by chromogenic substrates in response to drug treatment or during cell maturation - Theobald, Jannick; Cheng, Xinlai; Ghanem, Ali; Gaitantzi, Haristi; Breitkopf-Heinlein, Katja; Dooley, Steven; Wölfl, Stefan (Archives of toxicology, 2018)
The metabolic activity of hepatocytes is a central prerequisite for drug activity and a key element in drug-drug interaction. This central role in metabolism largely depends on the activity of the cytochrome P450 (CYP450) enzyme family, which is not only dependent on liver cell maturation but is also controlled in response to drug and chemical exposure. Here, we report the use of VividDye fluorogenic CYP450 substrates to directly measure and continuously monitor metabolic activity in living hepatocytes. We observed time- and dose-dependent correlation in response to established and putative CYP450 inducers acting through the aryl hydrocarbon receptor and drug combinations. Using repetitive addition of VividDye fluorogenic substrate on a daily basis, we demonstrated the new application of VividDye for monitoring the maturation and dedifferentiation of hepatic cells. Despite a lack of high specificity for individual CYP450 isoenzymes, our approach enables continuous monitoring of metabolic activity in living cells with no need to disrupt cultivation. Our assay can be integrated in in vitro liver-mimetic models for on-line monitoring and thus should enhance the reliability of these tissue model systems.
Gesehen am 11.04.2018
Article was first published online on 5 December 2017